Activity and substrate specificity of lytic polysaccharide monooxygenases: An ATR FTIR‐based sensitive assay tested on a novel species from Pseudomonas putida. (20th December 2021) - Serra, Ilenia; Piccinini, Daniele; Paradisi, Alessandro; Ciano, Luisa; Bellei, Marzia; Bortolotti, Carlo Augusto; Battistuzzi, Gianantonio; Sola, Marco; Walton, Paul H.; Di Rocco, Giulia
Abstract: Pseudomonas putida W619 is a soil Gram‐negative bacterium commonly used in environmental studies thanks to its ability in degrading many aromatic compounds. Its genome contains several putative carbohydrate‐active enzymes such as glycoside hydrolases and lytic polysaccharide monooxygenases (PMOs). In this study, we have heterologously produced in Escherichia coli and characterized a new enzyme belonging to the AA10 family, named Pp AA10 (Uniprot: B1J2U9), which contains a chitin‐binding type‐4 module and showed activity toward β‐chitin. The active form of the enzyme was produced in E. coli exploiting the addition of a cleavable N‐terminal His tag which ensured the presence of the copper‐coordinating His as the first residue. Electron paramagnetic resonance spectroscopy showed signal signatures similar to those observed for the copper‐binding site of chitin‐cleaving PMOs. The protein was used to develop a versatile, highly sensitive, cost‐effective and easy‐to‐apply method to detect PMO's activity exploiting attenuated total reflection‐Fourier transform infrared spectroscopy and able to easily discriminate between different substrates.